2018
DOI: 10.31139/chnriop.2018.83.2.12
|View full text |Cite
|
Sign up to set email alerts
|

Functional and psychological evaluation of patients enrolled into total knee arthroplasty and its effect on the treatment outcome – preliminary reports

Abstract: Introduction. In knee osteoarthritis, the treatment of choice is knee arthroplasty. The primary indication to perform TKA -Total Knee Arthroplasty is pain preventing the functioning of the patient. Aim. The main aim of this study was the assessment of the effects of knee osteoarthritis treatment of patients undergoing arthroplasty and the influence of psychological and physical factors in predicting pain and knee function after treatment. Material and methods. The study involved 60 patients between the ages of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Pain sensation may be influenced by pain interpretation and depression [42]. The study involving patients enrolled for total knee arthroplasty showed a correlation of lower pain level with better psychological condition postoperatively [43].…”
Section: Discussionmentioning
confidence: 99%
“…Pain sensation may be influenced by pain interpretation and depression [42]. The study involving patients enrolled for total knee arthroplasty showed a correlation of lower pain level with better psychological condition postoperatively [43].…”
Section: Discussionmentioning
confidence: 99%